Application of Simple Additive Weighting Method To Design an Employee Performance Assessment System in a National Logistics Company - Kus Yunanto, Mohammad; Ramayanti Sinaga, Herty; Violin, Vivid; Kespandiar, Tengku; Diawati, Prety (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to discover how an employee performance appraisal system using the website-based SAW method can help managers carry out the employee performance appraisal process. The method used in developing a web-based decision-making system is the prototype method. For data collection, two techniques were used. First, obtain the necessary information through interviews. Second, by collecting performance assessment data previously carried out manually by managers. It can be observed that the system may function effectively by performing its functions as an employee performance assessment utilizing the simple additive weighting calculation technique after creating a prototype decision-making system using the website-based simple additive weighting method. After managers have completed an evaluation, website-based solutions can combine data to make it easier to access, preserve data security, and support decision-making. The results provided yield high accuracy based on the SAW formula. This system uses the SAW calculation method so that employee performance assessments are carried out based on the percentage weight of the criteria that the manager has determined. From the requirements and results of this assessment, SAW can produce a ranking of employees with the best to worst performance. From this ranking, the manager can determine the employee with the best and worst performance, and then managers can make decisions based on that data.